2022
DOI: 10.1002/smll.202201137
|View full text |Cite
|
Sign up to set email alerts
|

In‐Plane Mott–Schottky Effects Enabling Efficient Hydrogen Evolution from Mo5N6‐MoS2 Heterojunction Nanosheets in Universal‐pH Electrolytes

Abstract: Cost‐effective electrocatalysts for the hydrogen evolution reaction (HER) spanning a wide pH range are highly desirable but still challenging for hydrogen production via electrochemical water splitting. Herein, Mo5N6‐MoS2 heterojunction nanosheets prepared on hollow carbon nanoribbons (Mo5N6‐MoS2/HCNRs) are designed as Mott–Schottky electrocatalysts for efficient pH‐universal HER. The in‐plane Mo5N6‐MoS2 Mott–Schottky heterointerface induces electron redistribution and a built‐in electric field, which effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…Among the common transition metalbased electrocatalysts such as sulfides, carbides, phosphides, and nitrides, [8][9][10][11][12][13] 2D molybdenum disulfide (MoS 2 ) has attracted much attention because of the earth's abundance and Pt-like hydrogen adsorption free energy (ΔG H* ). [14][15][16][17][18][19] However, the HER activity of MoS 2 is limited by the small number of unsaturated edge sites and poor intrinsic conductivity. [20][21][22][23] It is demonstrated that S-vacancies (S v ) in the inert basal plane can enhance the HER kinetics by exposing more unsaturated S-Mo bonds to optimize ΔG H* on the MoS 2 surface and various strategies have thus been proposed to generate S v in the basal plane, for example, etching with H 2 O 2 , [24] NaClO, [25] oxygen plasma treatment, [26] as well as H 2 annealing.…”
Section: Doi: 101002/smll202203173mentioning
confidence: 99%
“…Among the common transition metalbased electrocatalysts such as sulfides, carbides, phosphides, and nitrides, [8][9][10][11][12][13] 2D molybdenum disulfide (MoS 2 ) has attracted much attention because of the earth's abundance and Pt-like hydrogen adsorption free energy (ΔG H* ). [14][15][16][17][18][19] However, the HER activity of MoS 2 is limited by the small number of unsaturated edge sites and poor intrinsic conductivity. [20][21][22][23] It is demonstrated that S-vacancies (S v ) in the inert basal plane can enhance the HER kinetics by exposing more unsaturated S-Mo bonds to optimize ΔG H* on the MoS 2 surface and various strategies have thus been proposed to generate S v in the basal plane, for example, etching with H 2 O 2 , [24] NaClO, [25] oxygen plasma treatment, [26] as well as H 2 annealing.…”
Section: Doi: 101002/smll202203173mentioning
confidence: 99%
“…The construction of heterojunctions can afford a larger surface area, accelerate the electron transfer at the interface and regulate the adsorption free energy of reaction intermediates. [29][30][31][32] Thus, the rational design of bimetallic heterojunctions is a promising approach to boost the catalytic activity of metal nitrides. Recently, nickel nitride-based heterojunctions are widely developed, such as Ni 3 N/Co 2 N, NiMoN/ Ni 3 N, and Ni 3 N/W 5 N 4 heterostructures, and Ni 0.2 Mo 0.8 N/Fedoped Ni 3 N nanosheet arrays, exhibiting promising catalytic activity for water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…3(a)) spectrum of MoS 2 is assigned to two strong peaks at 162.3 and 163.5 eV, consistent with S 2p 3/2 and S 2p 1/2 , respectively. 38 Differently, the peaks of Mo 3d and S 2p of the RuO 2 /MoS 2 catalyst both shift positively with a new peak at 235.2 eV assigned to Mo 6+ and a new signal at 168.4 eV attributed to SO 4 , 2–40 which suggests that electrons transfer from MoS 2 to RuO 2 nanoparticles, resulting from the intense electronic coupling effect generated from interface modifications. Furthermore, in the Ru 3d spectrum of the RuO 2 /MoS 2 catalyst (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Compared to the Raman peaks of MoS 2 , RuO 2 /MoS 2 displays a red-shift, which demonstrates the formation of an interface between RuO 2 nanoparticles and MoS 2 nanosheets with strong electronic interaction. 9 The chemical compositions and valence state were examined in depth by X-ray photoelectron spectroscopy (XPS). The full-scan X-ray photoelectron spectroscopy of the RuO 2 /MoS 2 catalyst confirms the coexistence of the Mo, S, Ru, and O elements (Fig.…”
Section: Resultsmentioning
confidence: 99%